A carbon price floor in the reformed EU ETS: Design matters! - Martin Hintermayer (Institute of Energy Economics at the University of Cologne (EWI), 2020)
Despite the reform of the European Emissions Trading System (EUETS), discussions about complementing it with a carbon price floor (CPF) are ongoing. This paper analyzes the effect of a European CPF in the reformed EUET Susinga Hotelling model of the EUETS, amended by the market stability reserve(MSR), and the cancellation mechanism. Two CPF designs are compared: (1) a buyback program and (2) a top-up tax. The buyback program sets a minimum price for the allowances from the implementation year onwards. After the announcement, firms anticipate the CPF, which immediately increases the carbon price to the discounted CPF level. Therefore, firms emit less and bank more allowances,leading to more intake into the MSR,and more cancellation of allowances. The top-up tax imposes a tax on emissions, which enhances the market price of allowances to the CPF level from the implementation year onwards. Firms increase their short-run emissions in anticipation of the upcoming tax. Only after the implementation year firms start to lower their emissions. Thus, the effect on aggregate cancellation is ambiguous. Despite being equivalent in a static setting, the design choice for the CPF matters in a dynamic context, such as the EUETS.
Keywords: H23; H32; Q58; 330; Intertemporal Emission Trading; Carbon Price Floor; EUETS